HUMAN RIGHTS AI ASSISTANTS: EMPOWERING GLOBAL CITIZENS IN THE DIGITAL AGE - Karadimche, Aleksandar; Skender, Fehmi; Ilovski, Jovan (International Scientific Journal Vision, 2025)
Artificial Intelligence (AI) can dramatically redefine the parameters of human rights. With the appropriate application of AI, specifically through the usage of large language models, we can automate systems that help individuals protect and advocate for their digital rights. These assistants can help with the legal aspect and privacy issues as well as reporting any human rights violation. However, such developments also raise some other issues that have to be resolved in the first place, such as the bias and equity in the data, the credibility of the information, and the privacy of data. These challenges have to be carefully taken into consideration. The goal of this research is to contribute to the understanding of the role of AI in the human rights advocacy. Developing and creating AI agents that are purpose-built and trained on a customized dataset of human rights will assist in providing more efficient assistance to individuals. By combining AI with human expertise, we can create a powerful tool for advancing human rights in the digital age.